Some problems of a theory of reference - Kozachenko, Nadija (Actual Problems of Mind, 2017)
The paper considers some problems of the modern theory of reference, and analyses its sources and directions. The author sketches some prospects in development of the theory of reference from a standpoint of ontological adequacy.